UKRAINIAN MARSEILLAISE BY TARAS SHEVCHENKO SUMMARY - Крючков, Георгій (Київський національний університет імені Тараса Шевченка, 2020)
The article is devoted to the analysis of dіfferent translations of Taras Shevchenko «Testament» and National French Himn Marseillaise. Two value systems and specific psycholects of nostalgia, aggression, peace are examined. The aim of the article is to define the main psycholects in Taras Shevchenco poems, particularly in «Testament». In result of the comparison methods of several translations of «Testament» we have obtained three important psycholect of nostalgia, aggression and peace. All spheres use the concept of «love» and «mother country». The first and the second quatrains of «Testament» contain the invincible, calm, tranquil grandeur and beauty of the peace-loving country. Both quatrains are based on the psycholect nostalgia. The third and the fourth quatrains are the most discussed but they impresse everybody with their optimism, future of Ukraine, belief, victory, liberty. In the fifth quatrain the poet calls Ukrainians to revolt and to win the liberty. The psycholect of this quatrain ensures the riot and the victory. This is the psycholect of aggression. The sixth quatrain describes the future of Ukraine. The poet asks to recollect him in the new society, in the new, big and free family. The psycholect of peas ensures the ideal calm in the society of free people.  The conceptosphere of the first and the second quatrains of «Testament» is founded on nostalgia's concept «Love» and «Mother country». Lexical means, grammatical structure of phrases, phonetic phenomenos and prosody provide with intellectual, logical and emotional expression of feelings in the poet's psycholect who was sick and took leave of the life and said good-bye to the Ukrainian people. Concepts of the third and the fourth quatrains are God and Liberty. Marseillaise has the same idea of the fight and the victory. The fifth quatrain follow the main concept of the struggle. Slogans of this quatrain coincide with appeals of Marseillaise: bury, rise, tear asunder chains, stain the freedom with blood. The image of enemy's blood on «Testament» corresponds to impure blood of Marseillaise. The interrogatory of students and teachers witnesses the main concept of «Testament» (95 per cent). This is «Freedom». The second concept is «Religion» (God. Pray) – 86 per cent. The third concept is «Motherland» - (toponyms: Ukraine, Dnipro) – 80 %. Strangers consider the main idea of «Testament» in the last quatrain. Ukrainian respondents consider more important adjectives about Family: free (45 per cent), new (41 per cent), big (14 per cent).   Important lines of Testament are the following: Tear chairs – 23 per cent. Bury and revolt – 19 per cent. Don’t forget to speak well – 19 per cent. Pray – 15 per cent. Enemy’s wicked blood – 5 per cent. Testament of Taras Shevchenko is just the second national himn of Ukraine or Ukrainian Marseillaise. It is constructed on three psycholects: nostalgia, aggression and peace. The general harmony of this poem is attained by well–balance between aggression and peace.   ________________ Reference Andreev D.L. (1991). Roza mira. Metafilosofiia istorii [Rose of peace. Metaphilosophy of history]. – Moscow: Russiko [in Russian]. Barabash Yu. (2011). Prostorin Shevchenkovoho Slova [Space of Shevchenko's words]. Kyiv: Tempora [in Ukrainian]. Trotskyi L. (1990). Instruktsiia ahitatoram kommunistam na Ukrainie (Rech Narodnoho Komissara tov. Trotskoho k kursistkam (sic!) [Speech of people's commissar comrade Trotskyi to apprentices [sis!])]. Jurnal "Kyiv" – "Kyiv", 12, 113-115 [in Russian]. Doroshenko D. (1942). Istoriia Ukrainy [History of Ukraine].–Lviv: Ukrainske vydavnytstvo Krakiv [in Ukrainian]. Kriuchkov H.H. (2007) Peredmova // Tkachenko A. Ukrainsko-frantsuzki zviazky v osobah, podiiah ta legendah [Ukrainian and French relations in persons, events and legends]. – Luhansk^ Shiko, pp. 7-9 [in Ukrainian]. Nalyvaiko D.S. (2000). Istoriia i mifologiia u Shevchenka: u konteksti evropeiskoho romantyzmu [History and myphology of Shevchenko:in context of European romantism]. Taras Shevchenko: evropeiska kultura – Taras Shevchenko: European culture, Kyiv – Cherkassy, p. 20 [in Ukrainian]. Farion I. (2012). Voroh nikoly sam ne zhyne, iak rosa na sontsi [The enemy will never perish as dew in the sun]. Derjava 2000 – State 2000, 23 (609), pp. 2-3 [in Ukrainian]. Tsalai-Jakymenko O.S. (1963) "Zapovit" T.H.Shevchenka – narodna revoliutsiina pisnia ["Testament" of T.H.Shevchenko is the national and revolutionary song]. Narodna tvorchist ta etnografia – Folk works and ethnographics, 1, pp. 3-11 [in Ukrainian]. Shevchenkivska entsyklopediia: u 6 Vols (2015). [Shevchenko's encyclopedia: in 6 Vols (2015)], Vols 6: T–YA, NAN of Ukraine [in Ukrainian]. Shevchenko T.H. (1989). Povne zibrannia tvoriv: u 12 Vols [Complete works: 12 Vols]. Kyiv: Naukova dumka [in Ukrainian]. Cherednychenko O.I. (2014). Shevchenko u frankomovnomu sviti [Shevchenko in francophone world]. Shevchenkoznavstvo u suchasnomu sviti – Shevchenko's studies in the modern world, Vols 6, pp. 279-298 [in Ukrainian]. Shevchenko T.H. (1952) "Yak umry, to pokhovaite..." [When I die, bury me...]. Kobzar – Kobzar, Vols 2 (pp. 298-300), Vinnipeh, Tryzub [in Ukrainian]. Marseillaise (1980) [Marseillaise]. Le Français sans peine – French without difficulty, Lesson 41, p. 13 [in French].

У статті зіставлено різні переклади «Заповіту» Тараса Шевченка і Національного гімну Франції Марсельєзи. Проаналізовано дві ціннісні системи та специфічні психолекти ностальгії, агресії, умиротворення. Актуальність статті зумовлено значенням поетичних творів поета для розбудови незалежної і вільної України. Мета полягає у визначенні основних психолектів поета та їх співвідношення. Перший та другий катрени «Заповіту» містять непереможну, спокійну, тиху велич і красу образів Батьківщини поета. Вони ґрунтуються на ностальгічному психолекті. Третій та четвертий катрени є найбільш дискусійними, але при цьому вражають кожного своєю бадьорістю, силою віри в майбутнє України, її визволення від ворогів. У п’ятому катрені поет закликає український народ встати й здобути собі волю. Психолект цього катрену акцентує бунтівний образ. У шостому, останньому катрені поет просить згадати його в сім'ї великій, вольній, новій. Психолект умиротворення забезпечує ідеальний спокій у громаді вільних людей. Загальна гармонійність звучання цього поетичного шедевру досягається урівноваженням між мотивами агресії та умиротворення. У подальших дослідженнях будуть проаналізовані психолекти поетичних творів Тараса Шевченка, політичних діячів України і Франції. ___________ Список використаних джерел Андреев Д. Л. Роза мира. Метафилософия истории / Д. Л. Андреев. – М., 1991. – 288 с. Барабаш Ю. Просторінь Шевченкового Слова / Ю. Барабаш. – К., 2011. – 501 с. Десять заповідей. Инструкция агітаторам-коммунистам на Украинъ (Речь Народного Комиссара тов. Троцкого к курсисткам [siс!]) // Київ. – No 12. – 1990. – С. 113–115. Дорошенко Д. Історія України. – Львів, 1942. – 252 с. Крючков Г. Г. Передмова / Г. Г. Крючков // Ткаченко А. Українсько-французькі зв'язки в особах, подіях та легендах. – Луганськ, 2007. – С. 7–9. Наливайко Д. С. Історія і міфологія у Шевченка: у контексті європейського романтизму / Д. С. Наливайко // Тарас Шевченко: європейська культура. – К., 2000. – С. 20. Фаріон І. "Ворог ніколи сам не загине, як роса на сонці" / І. Фаріон // Держава 2000. – No 23(609). – 2012. – С. 2–3. Цалай-Якименко О. С. "Заповіт" Т. Г. Шевченка – народна революційна пісня / О. С. Цалай-Якименко // Народна творчість та етнографія. – 1963. – No 1. – С. 3–11. Шевченківська енциклопедія : в 6 т. / редкол. : М. Г. Жулинський (гол.) та ін. – К., 2015. – T. 6. – 1120 с. Шевченко Т. Г. Повне зібр. творів : у 12 т. – К., 1989. – Т. 1. – С. 528. Шевченкознавство в сучасному світі / Н. Л. Білик, І. П. Бондаренко, Г. Г. Верба та ін. – К., 2014. – 463 с.
УКРАЇНСЬКА МАРСЕЛЬЄЗА ТАРАСА ШЕВЧЕНКА
Keywords: рsycholect; nostalgia; aggression; peace; concept; психолект; ностальгія; агресія; умиротворення; концепт